Stroke - Hennerici, Michael G. (OUP Oxford, 2012)
Stroke is the third most common cause of death after heart disease and cancer in developed countries. Part of the Oxford Neurology Library, this pocketbook highlights the importance of stroke, its diagnosis, the problems of misdiagnosis, and current thoughts on its pathogenesis, acute treatment and rehabilitation as well as prevention. The book will serve as an invaluable quick reference for neurologists, cardiologists, geriatricians, internists, trainees, nurses, allied health professionals, and general practitioners
Description based upon print version of record
Keywords: Electronic books